PENGARUH MOTIVASI KERJA DAN PELATIHAN TERHADAP KINERJA KARYAWAN PADA DINAS PEKERJAAN UMUM PROVINSI KALIMANTAN TIMUR - Heriyanto, Hetty Fitriyani, H. Eddy Soegiarto K (EKONOMIA, 2015)
The problem in this study is whether the motivation and training factors significantly influence the performance of Public Works Department Employee of East Kalimantan Province, while the purpose of this study was to determine the effect of work Motivation on Employee Performance and Training Department of Public Works East Kalimantan Province.Basic theory used is Human Resource Management by using multiple linear regression analysis with 84 samples.The results showed:1   F count> F table and significance 0.000 <α = 0.05, which means that together work motivation and training variables have a significant influence on the performance of employees of Public Works Department of East Kalimantan.2   Partially show work motivation variable (X1) has influence on the performance of employees sifnifikan Public Works Department East Kalimantan (Y) which is indicated by the results of the calculation of the value t> t table and significance 0.016 <0.05, which means that if the provision of work motivation improved the performance of the employee will increase as well thus the research hypothesis is accepted.3  Partially show training variables (X2) has influence on the performance of employees sifnifikan Public Works Department East Kalimantan (Y) which is indicated by the results of the calculation of the value t> t table and significance 0.000 <0.05. This suggests that if the training gets the attention it will encourage employee performance improvement thus the research hypothesis is accepted4  Furthermore, the partial indicates that that the value of work motivation variable t <t variables of training means training variable than the variable dominant influence work motivation on employee performance Public Works Department of East Kalimantan Province, thus the hypothesis that allegedly dominant factors influence employee motivation the Department of Public Works employee performance province of East Kalimantan, was rejected